Academic burnout pada mahasiswa tingkat akhir: Bagaimana peranan prokrastinasi akademik dan academic burnout? - Faradita Marchella; Andik Matulessy; Nindia Pratitis (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to look at the relationship between Academic Burnout and Academic Procrastination. Academic Burnout is the independent variable in this study. While academic procrastination is the dependent variable. The sample of this research was final year students in the city of Surabaya with a total of 130 respondents. The sampling used is non-probability sampling with incidental sampling technique, which is a method of determination based on chance, that is, anyone who meets the researcher can be used as a sample, if it is deemed that person meets the appropriate criteria as a data source. Collecting research data using a questionnaire. Hypothesis testing was carried out with the results of a correlation coefficient of 0.178 with a significance level of p = 0.042 (p> 0.0) which showed a very significant positive relationship between academic burnout and academic procrastination, meaning that the higher the academic burnout, the higher the procrastination behavior of undergraduate students. finally in the city of Surabaya. Keywords: Academic Burnout, Academic Procrastination, Final Year Student Abstrak Penelitian ini bertujuan untuk melihat hubungan antara Academic Burnout dengan Prokrastinasi Akademik. Academic Burnout ini menjadi variabel independent pada penelitian ini. Sedangkan prokrastinasi akademik merupakan variabel dependen. Sampel penelitian ini adalah mahasiswa tingkat akhir di kota Surabaya sejumlah 130 responden. Pengambilan sampel yang digunakan yakni non probability sampling dengan Teknik incidental sampling, yaitu suatu metoe penentuan berdasarkan kebetulan, yaitu dengan siapa saja yang bertemu dengan peneliti dapat digunakan sebagai sampel, bilamana dipandang orang tersebut memenuhi kriteria yang sesuai sebagai sumber data. Pengumpulan data penelitian ini menggunakan kuisoner. Pengujian hipotesis yang dilakukan dengan hasil koefisien korelasi sebesar 0,178 dengan taraf signifikansi p = 0,042 (p>0.0) yang menunjukan hubungan positif yang sangat signifikan antara academic burnout dan prokrastinasi akademik, artinya semakin tinggi academic burnout, maka .semakin tinggi pula perilaku prokrastinasi pada mahasiswa tingkat akhir di kota Surabaya Kata kunci: academic burnout, prokrastinasi akademik, mahasiswa tingkat akhir